2006
DOI: 10.1128/jcm.00898-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Combination of Brushing Technique and the Loop-Mediated Isothermal Amplification Method as a Novel, Rapid, and Safe System for Detection of Helicobacter pylori

Abstract: Gastric mucosal biopsy is widely used in the detection of Helicobacter pylori but is associated with a number of problems, including false-negative results due to sampling error and massive bleeding after biopsy. Given the extended period required to culture H. pylori, detection would be further improved by the use of rapid detection methods such as PCR. Here, we developed a rapid, safe, and convenient method for collecting H. pylori which combines endoscopic brushing with the loop-mediated isothermal amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…The number of positive results for DGS, culture and RUT in gastric mucus specimens decreased by 22.2 , 19.8 and 9.9 %, respectively, compared to those in antral biopsy specimens (Table 2). However, Minami et al (2006) have reported that combination of the endoscopic brushing technique with the loop-mediated isothermal amplification method is a useful and safe system for identifying H. pylori infection.…”
Section: Resultsmentioning
confidence: 99%
“…The number of positive results for DGS, culture and RUT in gastric mucus specimens decreased by 22.2 , 19.8 and 9.9 %, respectively, compared to those in antral biopsy specimens (Table 2). However, Minami et al (2006) have reported that combination of the endoscopic brushing technique with the loop-mediated isothermal amplification method is a useful and safe system for identifying H. pylori infection.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the increase in the turbidity of the reaction mixture according to the production of precipitate correlates with the amount of DNA synthesized [10,11]. Various LAMP assays for the identification of pathogenic organisms have been developed [10][11][12][13]15,16], however, no assay for the detection of CT-producing V. cholerae has been described.…”
Section: Introductionmentioning
confidence: 99%
“…LAMP products could be detected & M. Parani parani.m@ktr.srmuniv.ac.in 1 visually by turbidity or by using fluorescent dyes such as ethidium bromide, calcein, and SYBR Green [13]. LAMP was successfully established as a tool for detecting pathogenic bacteria and viruses from clinical and environmental samples [14][15][16][17][18][19]. LAMP was used to detect the NDM-1 gene in sputum, urine and fecal samples [20].…”
Section: Introductionmentioning
confidence: 99%